2005
DOI: 10.1038/nature04222
|View full text |Cite
|
Sign up to set email alerts
|

Mapping stem cell activities in the feather follicle

Abstract: It is important to know how different organs 'manage' their stem cells. Both hair and feather follicles show robust regenerative powers that episodically renew the epithelial organ. However, the evolution of feathers (from reptiles to birds) and hairs (from reptiles to mammals) are independent events and their follicular structures result from convergent evolution. Because feathers do not have the anatomical equivalent of a hair follicle bulge, we are interested in determining where their stem cells are locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
158
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(160 citation statements)
references
References 30 publications
2
158
0
Order By: Relevance
“…Our recent work on the mapping of feather stem cells shows that the different relative positioning of stem cells and transient amplifying cells (TA cells in ectodermal organogenesis terminology; they are also defined by a short BrdU labeling and are equivalent to the LoGZ here) can lead to different feather morphologies. Specifically, stem cells are configured as a ring, positioned horizontally in the radially symmetric downy feathers but tilted anteriorly in bilaterally symmetric feathers (Yue et al, 2005). An anterior-posterior Wnt 3a gradient is critical for forming the bilateral but not radial symmetry of feathers (Yue et al, 2006).…”
Section: Multicomponent Multi-logz Morphogenesis Of the Beak And Thementioning
confidence: 99%
“…Our recent work on the mapping of feather stem cells shows that the different relative positioning of stem cells and transient amplifying cells (TA cells in ectodermal organogenesis terminology; they are also defined by a short BrdU labeling and are equivalent to the LoGZ here) can lead to different feather morphologies. Specifically, stem cells are configured as a ring, positioned horizontally in the radially symmetric downy feathers but tilted anteriorly in bilaterally symmetric feathers (Yue et al, 2005). An anterior-posterior Wnt 3a gradient is critical for forming the bilateral but not radial symmetry of feathers (Yue et al, 2006).…”
Section: Multicomponent Multi-logz Morphogenesis Of the Beak And Thementioning
confidence: 99%
“…Recent studies have suggested that the ramogenic plane becomes tilted in pennaceous feathers, so that the growth of barb ridges determines their fusion into a rachis (Yue et al 2005(Yue et al , 2006. The change in orientation of the ramogenic plane may be derived from unknown messages probably coming from the dermal papilla.…”
Section: Rachis Formationmentioning
confidence: 99%
“…It has been proposed (Yue et al 2005(Yue et al , 2006) that in downfeathers the ramogenic plane is horizontal so that growing barb ridges remain separated and implanted in a basal calamus (Figures 8 AA1, A2, A3; different colours indicate successive addition of Figure 6. Cross-section of upper follicle of asymmetric chicken wing feathers.…”
Section: Rachis Formationmentioning
confidence: 99%
See 2 more Smart Citations